Improving Children's Cognitive Abilities with Playing Simple Math and Science - Lestari, Wahyuni Puji (Journal of Childhood Education, Development and Parenting, 2023)
Playing with math and science for children are not only interesting but also can increase creativity and increase cognitive skill. Playing math to childhood are introduce beginning basic math concept by interesting playing. In daily life, the childhood can introduce and study math very simple. Starting from look their finger than learn to count its. When the children share the cake with their friends, it’s also introduce math concept. In daily, the children are nearing from the world of mathematics, but almost of us, understanding math only about number, summary, reduction, multiplication, arithmetic, etc. even though many early mathematical concepts are close to the world of children. By introducing the basic concept of mathematics from an early age will be able to have life skills for their future, because almost of human life are related to mathematics concept. In addition to basic math concepts, early childhood also needs to know about the world of science. Playing science in early childhood is an effective learning to recognize the world around him with the five senses of them.